Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

Long-term climatological and ecohydrological analysis of a paired catchment – flux tower observatory near Dresden (Germany). Is there evidence of climate change in local evapotranspiration? - T. Pluntke; C. Bernhofer; T. Grünwald; M. Renner; H. Prasse (Journal of Hydrology, 2023)

Uncovering the critical soil moisture thresholds of plant water stress for European ecosystems - Zheng Fu; Philippe Ciais; David Makowski; Ana Bastos; Paul C. Stoy; Andreas Ibrom; Alexander Knohl; Mirco Migliavacca; Matthias Cuntz; Ladislav Šigut; Matthias Peichl; Denis Loustau; et al. (Global Change Biology, 2022)
Understanding the critical soil moisture (SM) threshold (θ crit ) of plant water stress and land surface energy partitioning is a basis to evaluate drought impacts and improve models for predicting future ecosystem condition and climate. Quantifying the θ crit across biomes and climates is challenging because observations of surface energy fluxes and SM remain sparse. Here, we used the latest database of eddy covariance measurements to estimate θ crit across Europe by evaluating evaporative fraction (EF)‐SM relationships and investigating the covariance between vapor pressure deficit (VPD) and gross primary production (GPP) during SM dry‐down periods. We found that the θ crit and soil matric potential threshold in Europe are 16.5% and −0.7 MPa, respectively. Surface energy partitioning characteristics varied among different vegetation types; EF in savannas had the highest sensitivities to SM in water‐limited stage, and the lowest in forests. The sign of the covariance between daily VPD and GPP consistently changed from positive to negative during dry‐down across all sites when EF shifted from relatively high to low values. This sign of the covariance changed after longer period of SM decline in forests than in grasslands and savannas. Estimated θ crit from the VPD–GPP covariance method match well with the EF–SM method, showing this covariance method can be used to detect the θ crit . We further found that soil texture dominates the spatial variability of θ crit while shortwave radiation and VPD are the major drivers in determining the spatial pattern of EF sensitivities. Our results highlight for the first time that the sign change of the covariance between daily VPD and GPP can be used as an indicator of how ecosystems transition from energy to SM limitation. We also characterized the corresponding θ crit and its drivers across diverse ecosystems in Europe, an essential variable to improve the representation of water stress in land surface models.

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

High-altitude water budgets: ecological and hydrological forest research in view of landscape modelling - R. Matyssek; C. Bernhofer; B. Huwe (European Journal of Forest Research, 2009)

Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - N. DELPIERRE; K. SOUDANI; C. FRANÇOIS; B. KÖSTNER; J.‐Y. PONTAILLER; E. NIKINMAA; L. MISSON; M. AUBINET; C. BERNHOFER; A. GRANIER; T. GRÜNWALD; B. HEINESCH; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m −2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m −2 anomaly over 5 months), leading to higher net uptake than the long‐term mean at all sites (+12 to +79 gC m −2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process‐based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

The Energy Balance Experiment EBEX-2000. Part III: Behaviour and quality of the radiation measurements - W. Kohsiek; C. Liebethal; T. Foken; R. Vogt; S. P. Oncley; Ch. Bernhofer; H. A. R. Debruin (Boundary-Layer Meteorology, 2007)

Estimating the components of the sensible heat budget of a tall forest canopy in complex terrain - U. Moderow; C. Feigenwinter; C. Bernhofer (Boundary-Layer Meteorology, 2007)

Editorial: Progress in urban climate - T. Oke; K. Kłysik; C. Bernhofer (Theoretical and Applied Climatology, 2006)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

Comparing CO2 Storage and Advection Conditions at Night at Different Carboeuroflux Sites - M. Aubinet; P. Berbigier; Ch. Bernhofer; A. Cescatti; C. Feigenwinter; A. Granier; Th. Grünwald; K. Havrankova; B. Heinesch; B. Longdoz; B. Marcolla; L. Montagnani; et al. (Boundary-Layer Meteorology, 2005)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

The Influence of Advection on the Short Term CO 2 -Budget in and Above a Forest Canopy - C. Feigenwinter; C. Bernhofer; R. Vogt (Boundary-Layer Meteorology, 2004)

Evaluation of six process‐based forest growth models using eddy‐covariance measurements of CO 2 and H 2 O fluxes at six forest sites in Europe - K. Kramer; I. Leinonen; H. H. Bartelink; P. Berbigier; M. Borghetti; Ch Bernhofer; E. Cienciala; A. J. Dolman; O. Froer; C. A. Gracia; A. Granier; T. Grünwald; et al. (Global Change Biology, 2002)
Reliable models are required to assess the impacts of climate change on forest ecosystems. Precise and independent data are essential to assess this accuracy. The flux measurements collected by the EUROFLUX project over a wide range of forest types and climatic regions in Europe allow a critical testing of the process‐based models which were developed in the LTEEF project. The ECOCRAFT project complements this with a wealth of independent plant physiological measurements. Thus, it was aimed in this study to test six process‐based forest growth models against the flux measurements of six European forest types, taking advantage of a large database with plant physiological parameters. The reliability of both the flux data and parameter values itself was not under discussion in this study. The data provided by the researchers of the EUROFLUX sites, possibly with local corrections, were used with a minor gap‐filling procedure to avoid the loss of many days with observations. The model performance is discussed based on their accuracy, generality and realism. Accuracy was evaluated based on the goodness‐of‐fit with observed values of daily net ecosystem exchange, gross primary production and ecosystem respiration (gC m −2 d −1 ), and transpiration (kg H 2 O m −2 d −1 ). Moreover, accuracy was also evaluated based on systematic and unsystematic errors. Generality was characterized by the applicability of the models to different European forest ecosystems. Reality was evaluated by comparing the modelled and observed responses of gross primary production, ecosystem respiration to radiation and temperature. The results indicated that: Accuracy . All models showed similar high correlation with the measured carbon flux data, and also low systematic and unsystematic prediction errors at one or more sites of flux measurements. The results were similar in the case of several models when the water fluxes were considered. Most models fulfilled the criteria of sufficient accuracy for the ability to predict the carbon and water exchange between forests and the atmosphere. Generality. Three models of six could be applied for both deciduous and coniferous forests. Furthermore, four models were applied both for boreal and temperate conditions. However, no severe water‐limited conditions were encountered, and no year‐to‐year variability could be tested. Realism. Most models fulfil the criterion of realism that the relationships between the modelled phenomena (carbon and water exchange) and environment are described causally. Again several of the models were able to reproduce the responses of measurable variables such as gross primary production (GPP), ecosystem respiration and transpiration to environmental driving factors such as radiation and temperature. Stomatal conductance appears to be the most critical process causing differences in predicted fluxes of carbon and water between those models that accurately describe the annual totals of GPP, ecosystem respiration and transpiration. As a conclusion, several process‐based models are available that produce accurate estimates of carbon and water fluxes at several forest sites of Europe. This considerable accuracy fulfils one requirement of models to be able to predict the impacts of climate change on the carbon balance of European forests. However, the generality of the models should be further evaluated by expanding the range of testing over both time and space. In addition, differences in behaviour between models at the process level indicate requirement of further model testing, with special emphasis on modelling stomatal conductance realistically.

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.